Tungsten dichalcogenide WS2xSe2−2x films via single source precursor low-pressure CVD and their (thermo-)electric properties. Issue 17 (18th April 2023) - Sethi, V.; Runacres, D.; Greenacre, V.; Shao, Li; Hector, A. L.; Levason, W.; de Groot, C. H.; Reid, G.; Huang, R.
Abstract : A series of novel single source precursors, [WECl4 (E′ n Bu2 )] (E = S or Se; E′ = S or Se), are developed in this work to deposit stoichiometric WS2 x Se2−2 x (0 ≤ x ≤ 1) binary and ternary thin films. Abstract : Semiconducting transition metal dichalcogenides have gained increased interest as potential alternatives to graphene due to their tunable electronic bandgaps. In this study, we present the deposition of stoichiometric WS2 x Se2−2 x (0 ≤ x ≤ 1) binary and ternary thin films using the single source precursors, [WECl4 (E′ n Bu2 )] (E = S or Se; E′ = S or Se), via low-pressure chemical vapour deposition. Compositional and structural characterisations of the deposits have been performed by grazing-incidence X-ray diffraction, scanning electron microscopy, X-ray photoelectron spectroscopy, and Raman spectroscopy, confirming the phase purity and stoichiometry. Electrical characterisation via Hall measurements reveals high electrical conductivities for those films. Such high conductivity is likely related to Se and S vacancies in the films and can be tuned through an annealing process. The thermoelectric capabilities of the WS2 x Se2−2 x have been characterised with the use of variable-temperature Seebeck measurements, showing a peak power factor of 6 μW m −1 K −2 for the as-deposited WS2 film at 553 K.